Magnetic and ferroelectric properties, crystal and magnetic structures of SrFe11.9In0.1O19. (13th February 2020) - Turchenko, V A; Trukhanov, A; Trukhanov, S; Damay, F; Porcher, F; Balasoiu, M; Lupu, N; Chiriac, H; Bozzo, B; Fina, I; Waliszewski, J; Kostishyn, V G; et al.
Abstract: The structural investigations of SrFe11.9 In0.1 O19 compound synthesized by solid-state method have been carried by neutron diffraction method in a wide temperature range. The appearace of spontaneous polarization that coexists with ferrimagnetic ordering has been found out at room temperature in strontium hexaferrite partially substituted with In ions. In order to explaine the presence of ferroelectric properties in SrFe11.9 In0.1 O19 compound, its crystal structure has been refined within the framework of both centrosymmetric P63 /mmc (No. 194) and non-centrosymmetric P63 mc (No. 186) space groups. The analysis of refinement results allows to understand microscopic mechanism of appearance ferroelectric properties in strontium hexaferrites.